Users ' Attitudes and Usage Intentions towards Integration of Web 2.0 in Teaching and Learning Processes from Selected Universities in Tanzania - Kazoka, James Ernest (Papers in Education and Development, 2021)
Abstract This study examined users ' attitudes and intentions to integrate Web 2.0 technologies in teaching and learning activities. It was conducted in three Universities in Tanzania. The study employed a quasi-experimental design to faculty members and postgraduate students. Training was intended to involve faculty members and students on the use of Web 2.0 technologies. Data were collected using questionnaire and interviews from 24 faculty members and 30 students. The findings revealed that users ' attitudes towards the technology influence its integration into teaching and learning activities. The study therefore recommends organizing regular workshops with faculty members and students to raise their familiarity with Web 2.0 technologies and influence their attitude and intention to integrate technologies in teaching and learning activities. Keywords: behavioural intention, emerging technologies, use of Web 2.0 tools, users ' attitude, virtual Learning Introduction